This much is true - Lorret, Vivienne (Lorret, Vivienne. Liars' club, 2025)
"Althea Hartley has lost her spark. As the youngest daughter of an eccentric family, playwrighting is in her blood. But two failed Seasons have left her disenchanted. In desperate need of inspiration, she takes matters into her own hands by creating a tale of a dashing highwayman. What could possibly go wrong? But her stories prove to be a little too true for the actual highwayman living beneath the ton's nose. Jasper Trueblood, Viscount St. James, needs to put an end to the bewitching Miss Hartley's incriminating tales. Society can never suspect that he isn't the clumsy oaf he pretends to be. Or that, under the cover of darkness, he greets scoundrels and lightens their purses. Not too much. Just enough to keep those closest to him safe from his menacing uncle. Then sparks fly when this unlikely pair meets one perfect night. And while she is eager to unmask him, he is determined to stay hidden. But there's no denying the chemistry that neither of them are able to resist... The only thing for certain is that Thea needs to guard her heart before the highwayman steals it." -- Amazon.